1997
DOI: 10.1128/jb.179.10.3310-3316.1997
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a basic cell surface-located protein from Lactobacillus fermentum BR11

Abstract: Extraction ofCell surface polypeptides of gram-positive bacteria may be divided into a number of classes on the basis of the way in which they are anchored to the cell envelope. In two such classes, the LPXTG-containing proteins and the lipoproteins, attachment is covalent. The former are anchored to cell wall peptidoglycan via the threonine residue in the C-terminally located LPXTG motif (20), while the latter are anchored to cytoplasmic membrane lipids via the cysteine residue in the N-terminally located LXX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 37 publications
0
84
0
Order By: Relevance
“…26) In the case of MapA, this protein shows high relatedness to CnBP of L. reuteri NCIB 11951 19) and BspA of L. fermentum BR11. 27,28) These proteins are known for thier binding potential to type I collagen and fibronectin, which are known as the receptors of many pathogens, therefore these adhesion factors are believed to act as antagonistic competitors. Furthermore, Velraeds et al and Heinemann et al reported that a protein, the N-terminus of which was found to be 100% identical to CnBP and MapA, from L. fermentum RC-14 is able to compete against Enterococcus faecalis 1131 adherence.…”
Section: Discussionmentioning
confidence: 99%
“…26) In the case of MapA, this protein shows high relatedness to CnBP of L. reuteri NCIB 11951 19) and BspA of L. fermentum BR11. 27,28) These proteins are known for thier binding potential to type I collagen and fibronectin, which are known as the receptors of many pathogens, therefore these adhesion factors are believed to act as antagonistic competitors. Furthermore, Velraeds et al and Heinemann et al reported that a protein, the N-terminus of which was found to be 100% identical to CnBP and MapA, from L. fermentum RC-14 is able to compete against Enterococcus faecalis 1131 adherence.…”
Section: Discussionmentioning
confidence: 99%
“…BR11 efficacy is proposed to be mediated through its unique 7 cystine transport system [13,15,16]. This transport system is responsible for transporting exogenous cystine into the bacterial cell and expelling the thiol products, which diminish the effects of oxidative stress by detoxifying reactive oxygen species present [17].…”
Section: Lactobacillus Reuteri Br11 (Br11) Is a Bacterial Strain ((Fomentioning
confidence: 99%
“…For example, a plasmid DNA clone encoding the (76). Similarly, the CjaC and CjaA proteins of Campylobacter jejuni were identified by screening with antiserum raised against whole C. jejuni cells (58,59).…”
Section: Bacterial Abc Transporter Proteins Are Immunogenicmentioning
confidence: 99%